Exploring the interactive effect of dysfunctional sleep beliefs and mental health on sleep in university students - Karsan, Sameena; Kuhn, Tara; Ogrodnik, Michelle; Middleton, Laura E.; Heisz, Jennifer J. (Frontiers in Sleep, 2024)
Poor mental health is a known risk factor for poor sleep among university students; however, less is known about the role of dysfunctional sleep beliefs and its relation to mental health and sleep. Additionally, people of color (POC) students may experience unique stressors related to discrimination and inequalities which can contribute to mental health issues and in turn, influence their sleep. The present study evaluated the impact of dysfunctional sleep beliefs and poor mental health on a student's susceptibility to worse sleep and examined differences among POC. Methods: Post-secondary students completed a survey including the Insomnia Severity Index and the Dysfunctional Beliefs and Attitudes about Sleep Scale. Participants also completed questionnaires measuring symptoms of depression, anxiety, and perceived stress. Results: 1562 students were included in the analyses, 58% of which were POC. POC students had more dysfunctional sleep beliefs (p < .01) and worse insomnia severity (p < .01) compared to white students. Overall, greater dysfunctional sleep beliefs were significantly associated with worse symptoms of depression (b =1.521), anxiety (b =1.170), stress (b =1.370), and poor sleep (b =1.963) (ps < .001). Dysfunctional sleep beliefs also moderated the relation between poor mental health and sleep, specifically depression (p = .035) and anxiety (p = .007), by exacerbating sleep outcomes. Discussion: The results suggest that dysfunctional sleep beliefs may play a role in perpetuating poor mental health and sleep. Interventions to improve students' sleep and well-being focused on reframing dysfunctional sleep beliefs should be examined. with vulnerability to stress-related sleep disturbance in young adults. Behavioral sleep medicine, 9(2), 86-91.